Six Teacher Personalities That Students Preferred - Yosine Yulya Putri; Suci Ade Pajaria; Muchni Zalfa Sirin; Miftahurrahmah Miftahurrahmah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2022)
This study aims to explore what forms of teacher personality the participants like to educate. This study uses a qualitative method with a case study approach. Data sources were taken from twelve informants from five different elementary schools using an interview protocol. The results of the interviews were analyzed thematically using Miles and Huberman. The research findings show six teacher personalities that are liked by students. The six personalities are i) patient, ii) humorous, iii) not showing favoritism, iv) always giving advice, v) being compassionate, vi) having a good character noble, The results of this study can be used as teachers, prospective teachers, and parents as an illustration of the personality forms of teachers who are liked by students so that they try more to have that personality.